Education and Liberation - Austin, David (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2009)
AbstractDrawing on his personal experience as a university student in the 1990s as well as those of a little-known 1960s Montreal-based group, the Caribbean Conference Committee, Austin calls for a return of community education and to the idea that education has meaning and value on its own term. He argues that the joining of theory with practice represents a powerful tool in the struggle for social and economic justice and transformation.